Kyrgyz Republic : Enhancing Pro-poor Growth - World Bank (Washington, DC, 2013)
The goal of this report has been to assist the Kyrgyz authorities in designing and implementing their National Poverty Reduction Strategy (NPRS). An interim report focusing on the relation between growth and poverty, with detailed analysis o f transmission mechanisms in labor market and agricultural sector was presented to the authorities in August 2002. The interim report delivery was driven by the schedule of NPRS preparation. This final poverty assessment report expands the interim report by addressing key additional issues in the links between poverty and key public services such as energy, health, education, and social protection. The process o f producing this report has involved close collaboration with Natstatcom, training Kyrgyz researchers on poverty analysis, and commissioning eleven independent researchers to write background papers on various aspects o f poverty in the Kyrgyz Republic whose findings have been Incorporated selectively in this report. Analysis in this report goes through the year 2001, but collaborative work between the Bank and Kyrgyz teams on poverty diagnostics and assessment is an ongoing process.